IMPLEMENTASI MODEL STOKASTIK PADA PERMASALAHAN OPTIMASI PERSEDIAAN KELAPA PADA TINGKAT DISTRIBUTOR - DEWI, NOVI RUSTIANA; SUSANTI, EKA; SUPRIHATIN, BAMBANG; BIDARTI, AGUSTINA; ABELIA, SINTA ELPATRIKA; MASYITHAH, NEYSA ADIRATNA AGMI (E-Jurnal Matematika; Vol 9 No 1 (2020), 2020)
In the inventory system is given operational policies relating to product inventory control, such as how much is ordered, when to order with the aim of minimizing storage and ordering costs. Customer demand and lead time affect the inventory system. This study aims to determine the densitas distribution of demand data, total inventory costs and optimal coconut supply for the two order periods using the stochastic inventory model. Stochastic inventory models can be used if there is variable uncertainty. This paper discusses the optimization of coconut inventories using a stochastic model with uncertainty about demand and lead time. It is known that demand data is uniformly distributed, based on the realization value of random variable requests can be formed in 49 scenarios. Obtained an optimal total inventory cost for the two planning periods is Rp. 45,672,910, optimal supply for period one was 26031 coconuts. Inventory levels in two period for any scenarios are